1990
DOI: 10.21236/ada232418
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution, Excretion, and Hepatic Biotransformation of Microcystin-LR in Mice

Abstract: OMB No. 0704-0188 ?a. REPORT SECURITY CLASSIFICATION l a A 1 1b RESTRICTIVE MARKINGS Unclassified ELE TF 2a. SECURITY CLASSIFICATION AUIT I MAR 12 190t 3 DISTRIBUTION /AVAILABILITY OF REPORT 2b. DECLASSIFICATION DOWNGRA G EDU, 4. PERFORMING ORGANIZATION REPORT NUMBEW S. MONITORING ORGANIZATION REPORT NUMBER(S) 6a. NAME OF PERFORMING ORGANIZATION 6b. OFFICE SYMBOL 7a. NAME OF MONITORING ORGANIZATION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
2
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 9 publications
5
80
2
2
Order By: Relevance
“…In mice given a sublethal dose of microcystin LR (35 Ag/kg), the peak plasma concentration achieved was 428 nmol/L (21) compared with the IC 50 values of 5 and 39 nmol/L for microcystin LR in OATP1B1-and OATP1B3-transfected HeLa cells, respectively (Table 2). In addition, microcystin rapidly accumulates in the liver, with 70% of the total dose accumulating by 30 min after the injection (21). We have shown that the cytotoxic activity of microcystin LR is rapid, and although maximal activity was not seen until 6 h, a 1-h exposure showed significant levels of activity (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…In mice given a sublethal dose of microcystin LR (35 Ag/kg), the peak plasma concentration achieved was 428 nmol/L (21) compared with the IC 50 values of 5 and 39 nmol/L for microcystin LR in OATP1B1-and OATP1B3-transfected HeLa cells, respectively (Table 2). In addition, microcystin rapidly accumulates in the liver, with 70% of the total dose accumulating by 30 min after the injection (21). We have shown that the cytotoxic activity of microcystin LR is rapid, and although maximal activity was not seen until 6 h, a 1-h exposure showed significant levels of activity (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…On the contrary, low level of binding in fish plasma would increase the availability of MCs, while reduce metabolism half-life through transformation and excretion. It is generally acknowledged that liver is the primary target organ of MCs (Dawson 1998;Robinson et al 1991). Acute toxicity test using tritium-labeled MCs proved that the combination of mammals' liver to MCs were more effective than that of fish (Brooks and Codd 1987), while clearances of MCs in either fish liver or whole body were proved to be much faster than mammal (Williams et al 1995;Robinson 1990;Robinson et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Although the main target organ of MCLR is the liver and despite most of the toxin being excreted via biliar route, a small (9%) percentage of the toxin (free or conjugated with GSH and Cys) is also eliminated through the urine (Robinson et al, 1990;Ito et al, 2002). It should be noted that although MCLR metabolites are less toxic than non-metabolized toxin, they still maintain the inhibitory activity of protein phosphatases PP1 and PP2A (Ito et al, 2002).…”
Section: Discussionmentioning
confidence: 99%